Redefining criticality in a changing world: Combining domestic and global perspectives on enabling technologies - Henning Kroll; Chiara Ferrante (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
In a dynamic geopolitical environment, policy makers need additional types of information when selecting technological domains for specific support. While all such selections eventually become political, they need to remain evidence-based to shield them against capture. This paper argues that the prevalent, nationally agnostic approaches to identifying critical technologies has become too unidimensional to sufficiently inform political decisions. Subsequently, it proposes a method to sufficiently acknowledge specific domains' domestic embedding and provides an overview of how its application to leading nations' patent data enables us to identify characteristic technological systems and specific decision-making challenges in Europe, the US and China.
Keywords: 330; Redefining Criticality in a Changing World; Fraunhofer ISI; Enabling Technologies